Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability